Facilitating an Implementation of Online Portfolios in an EFL Writing Class - Warni, Silih (Journal of ELT Research, 2017)
This article presents part of a study on the implementation of online portfolios in an EFL writing class and is focused on the facilitation of online portfolio implementation. Students’ experiences in learning EFL writing using the online portfolios and my experiences in facilitating the online portfolio implementation were explored through action research. As for methods for generating data, this study involved students’ interviews, my reflective journals, and an analysis of students’ online portfolio entries. The study reveals that throughout the action research, problems emerged dealing with the use of a blog as the online portfolio platform, online feedback activities and students’ reflection. Some changes in the instructional plan were made throughout the three action research cycles in this study which include; guidance for peer feedback and reflection, organization of students’ online portfolios and procedure of peer commenting. The study suggests that the success of the online portfolio implementation in facilitating students’ learning of EFL writing requires teachers’ understandings of their own roles as well as their willingness to undertake and develop their roles as facilitators in an e-learning environment.